Pediatric liver transplant portal vein anastomotic stenosis: Correlation between ultrasound and transhepatic portal venography. Issue 4 (12th March 2015) - Hawkins, C. Matthew; Shaw, Dennis W. W.; Healey, Patrick J.; Horslen, Simon P.; Dick, Andre A. S.; Friedman, Seth; Shivaram, Giridhar M.
<x xml:space="preserve">Abstract</x> The objective of this study was to determine which transabdominal ultrasound parameters correlate with portal vein stenosis (PVS) on percutaneous transhepatic portal venography in pediatric liver transplant patients. A retrospective review was performed of percutaneous transhepatic portal venograms performed between 2005 and 2013. The findings were compared to those from ultrasounds performed before venography and at the baseline. Patients were stratified on the basis of the presence of significant PVS (group 1, >50% stenosis; group 2, ≤50% stenosis) on portal venography. Findings were compared to those for age‐matched controls. Twenty portal venograms were performed for 12 pediatric patients. Thirteen of the 20 patients (65%) demonstrated significant PVS (>50%). The mean peak anastomotic velocity (PAV) was 253.6 ± 96 cm/s in group 1, 169.7 ± 48 cm/s in group 2, and 51.3 ± 20 cm/s in the control group. PAV (r = 0.672, P = 0.002) was the only ultrasound variable that correlated with the presence of significant PVS. A receiver operating characteristic curve was generated from PAV and PVS data (area under the curve = 0.75, P = 0.08). A threshold velocity of 180 cm/s led to a sensitivity of 83% and a specificity of 71% in predicting significant PVS on portal venography. At the baseline, the mean PAV was 155.8 ± 90 cm/s for group 1 and 69.5 ± 33 cm/s for group 2 (P = 0.08); for control subjects, it was 78.9 ± 53 cm/s (P = 0.06). PAV is the only measured ultrasound parameter that correlates with significant PVS on portal venography in pediatric liver transplant patients. An elevated baseline PAV may increase the risk of developing PVS. Liver Transpl 21:547–553, 2015. © 2015 AASLD.